The 131 method : your personalized nutrition solution to boost metabolism, restore gut health, and lose weight - Johnson, Chalene (Hay House, Inc., 2019)
Your personalized plan for gut health, wellness, and weight loss You're smart. You're sick of gimmicks and trendy diets that leave you with frustration and a slower metabolism. The 131 Method gets to the root of the problem--gut health--and delivers a personalized solution to wellness, hormone balance, and permanent weight loss based on the Nobel Prize-winning science of autophagy and diet phasing. Finally, a science-based solution that's actually doable! Following her own health scare, health and wellness expert Chalene Johnson set out to understand the science and individuality of metabolism. Working with renowned researchers, doctors, and registered dietitians, she developed a simplified 3-phase plan for health promoting weight loss. This proven methodology was tested with more than 25,000 individuals. Now she distills the essentials of her hugely successful online program into the 131 Method book. 1 Objective (set by you!), 3 Weeks of Diet Phasing, and 1 Week to Fast and Refuel. 131 Method guides you through Chalene's three-phase, 12-week solution, helping you personalize every step of the way. You'll: *Lose weight without slowing your metabolism *Improve gut health and boost immunity *Fix cravings and reset hormones *Discover 100 delicious, easy recipes. The 131 Method isn't a one size fits all diet, it's how to eat a diet that works! You'll get everything you need to change your thinking, transform your body, and improve your life . . . for good!